Seropositivity of measles antibody- IgM in symptomatic pediatric patients with assessment of vaccination status in a tertiary care hospital - Sarkar, Kristi; Mullan, Summaiya (International Journal of Research in Medical Sciences, 2024)
Background: Measles is a febrile contagious viral illness caused by member virus of paramyxoviridae, commonly affecting paediatric population. It is a vaccine preventable disease. In spite of national immunisation programme in India, measles outbreaks are often encountered specially in pediatric population. This study aimed to assess the IgM seropositivity in acute cases of measles along with assessment of measles vaccination status. Methods: This study was conducted in a department of microbiology of Government Medical College, Surat from March, 2022 to March, 2023 in which pediatric patients with febrile suspected of measles were included. Serum samples were received and recording of clinical history and vaccination profile were done. The samples were investigated for measles IgM antibodies using enzyme-linked immunosorbent assay (ELISA). Results: Out of 90 pediatric febrile patients with suspected measles, 44 (49%) were found to be IgM measles positive. Among 44 IgM positive cases, 44% children were previously vaccinated and 45% children were not vaccinated. Information on vaccination status were not available for 11% children. Majority (43%) of IgM seropositive children were of age less than 2 years. Conclusions: In spite of ongoing national immunisation programme throughout the country, vaccination coverage is still not satisfactory and even if vaccinated, significant number of children are still getting infected with measles. Hence, studies are needed to identify the lacunae of ongoing programme and find out possible causes of lower vaccination protection.